Clinicopathological and Prognostic Significance of EML4-ALK Rearrangement in Patients with Surgically Resected Lung Adenocarcinoma: A Propensity Score Matching Study - Shi, Jinghan (Cancer Manag Res, 2020)
OBJECTIVE: The echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion gene is a key oncogenic driver in non-small cell lung cancer (NSCLC). This study analyzed the clinicopathological characteristics and prognostic significance of EML4-ALK fusion gene in patients with surgically resected adenocarcinoma. METHODS: The clinicopathological characteristics of 1056 consecutive patients with surgically resected stage I–IIIA adenocarcinoma were collected from February 2014 to October 2014, and EML4-ALK rearrangement was detected using real-time polymerase chain reaction (RT-PCR) technology. To compare the imaging and pathological features, a propensity score matching (PSM) method was performed. The follow-up information was collected to evaluate the long-term outcomes of patients with EML4-ALK rearrangement. RESULTS: The prevalence of EML4-ALK rearrangement was 6.6% in 1056 consecutive patients. A total of 70 EML4-ALK-positive and 210 EML4-ALK-negative patients were identified after PSM. Imaging and pathological analyses showed that EML4-ALK rearrangement was significantly associated with less ground-glass opacity (GGO) (adjusted OR=1.38, 95% CI=1.03–1.85, P(trend)=0.029) and higher prevalence of non-invasive mucinous adenocarcinoma mucin-laden adenocarcinomas (non-IMA MLA, adjusted OR=6.79, 95% CI=2.69–17.17, P<0.001). EML4-ALK rearrangement was found to be an unfavorable prognostic factor for disease-free survival (DFS) in female patients (HR=2.26, 95% CI=1.13–4.53, P=0.021). CONCLUSION: Our results suggest that adenocarcinomas harboring EML4-ALK fusion gene exhibit specific radiological and pathological characteristics compared with EML4-ALK-negative adenocarcinomas. In female patients, EML4-ALK rearrangement was associated with shorter DFS.